Kecenderungan kecanduan media sosial pada remaja: Adakah peran fear of missing out? - Trianti Agustina Lay; Tatik Meiyuntariningsih; Hetti Sari Ramadhani (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to prove that there is a positive correlation between the variable fear of missing out and the social media addiction tendency variable in adolescents. The participants in this study were 100 students from X Middle School in Gresik aged 13-16 years. The sampling technique in this study used a simple random sampling technique. Data analysis techniques in this study used IBM Statistics version 25 for windows. The results of the Spearman Rho non-parametric correlation test obtained a correlation coefficient of 0.671 with a significance of 0.000 (<0.05). Based on the results of the correlation test, it can be concluded that there is a significant positive correlation with the level of a strong relationship between the fear of missing out variable and the social media addiction tendency variable. This means that a positive relationship indicates that the higher the fear of missing out, the higher the tendency for social media addiction in adolescents. Vice versa, the lower the fear of missing out, the lower the tendency for social media addiction in adolescents. Keywords: Addiction, Social Media, Fear of Missing Out, Teenagers.